Exposure to e-cigarette advertising and its association with e-cigarette use among youth and adolescents in two largest cities in Vietnam 2020 - Thi Thanh Huong Le; Tu Hoang Le; Minh Dat Le; Tien Thang Nguyen (SAGE Publications, 2023)
BACKGROUND E-cigarette products have become more popular due to the marketing campaigns on various sources but caused adverse health impacts to users, especially adolescents and youths. This paper aims to describe the situation of exposure to e-cigarette advertisements of youth and adolescents living in two cities of Hanoi and Ho Chi Minh in 2020 and identify the associated factors of e-cigarette marketing with e-cigarettes use in these groups. METHODOLOGY This was a cross-sectional study. The study participants were 1211 youth and adolescents aged 15-24 living in Hanoi and Ho Chi Minh City during the time of data collection (from January 2020 to September 2020). Two primary outcome variables included the ever e-cigarettes use and the intention to use e-cigarettes. Multivariate logistic regression models were used to assess the association between the outcome variables and e-cigarette marketing exposure. RESULTS The proportion of participants who ever use e-cigarettes was 7.4% and a proportion of 4.8% have intention to use e-cigarettes. The most popular source of exposure to e-cigarettes advertisements was social network (Facebook, Twitter, Instagram, Youtube, etc.) and this source had positive association with the odds of e-cigarette smoking among youth and adolescents (OR = 3.38, 95% CI: 1.59-7.14). In addition, referral marketers also contributed to making the participants more likely to smoke e-cigarettes (OR = 2.68, 95% CI: 1.03-6.95). Attractive color and free sample of e-cigarettes were also found to be the motivated factors associated with smoking behaviour among youth and adolescents. CONCLUSIONS New policies should be considered to oppose the impact of youth-oriented e-cigarette advertisements which include regulating and restricting e-cigarette advertisements on social media, as well as through referral marketers.